Fabric along the NEEM ice core, Greenland, and its comparison with GRIP and NGRIP ice cores - Montagnat, M.; Azuma, N.; Dahl-Jensen, D.; Eichler, J.; Fujita, S.; Gillet-Chaulet, F.; Kipfstuhl, S.; Samyn, D.; Svensson, A.; Weikusat, I. (Freie Universität Berlin, 2014)
Fabric (distribution of crystallographic orientations) along the full NEEM ice core, Greenland was measured in the field by an automatic ice texture analyzer every 10 m, from 33 m down to 2461 m depth. The fabric evolves from a slightly anisotropic fabric at the top, toward a strong single maximum at about 2300 m, which is typical of a deformation pattern mostly driven by uniaxial compression and simple shearing. A sharp increase in the fabric strengthening rate is observed at the Holocene to Wisconsin (HW) climatic transition. From a simple model we estimate that this depth is located at a transition from a state dominated by vertical compression to a state dominated by vertical shear. Comparisons are made to two others ice cores drilled along the same ridge; the GRIP ice core, drilled at the summit of the ice sheet, and the NGRIP ice core, drilled 325 km to the NNW of the summit along the ridge, and 365 km upstream from NEEM. This comparison tends to demonstrate that the ice viscosity change with the HW climatic transition must be associated with the shear-dominated state to induce the abrupt fabric strengthening observed at NEEM. This comparison therefore reflects the increasing role of shear deformation on the coring site when moving NW along the ridge from GRIP to NGRIP and NEEM. The difference in fabric profiles between NEEM and NGRIP also evidences a stronger lateral extension associated with a sharper ridge at NGRIP. Further along the core, centimeter scale abrupt texture (fabric and microstructure) variations are observed in the bottom part of the core. Their positions are in good agreement with the observed folding layers in Dahl- Jensen et al. (2013).